2013
DOI: 10.5312/wjo.v4.i4.309
|View full text |Cite
|
Sign up to set email alerts
|

Current practice variations in the management of anterior cruciate ligament injuries in Croatia

Abstract: The results show that ACL reconstruction surgery in Croatia is in step with the recommendations from latest world literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 42 publications
5
21
0
Order By: Relevance
“…This supports previous studies that have identified activity demands and instability as important factors [1820]. Orthopaedic surgeons considered that a physically demanding occupation was a very important factor for recommending surgery (grading “3” twice as many times compared to “2”).…”
Section: Discussionsupporting
confidence: 88%
“…This supports previous studies that have identified activity demands and instability as important factors [1820]. Orthopaedic surgeons considered that a physically demanding occupation was a very important factor for recommending surgery (grading “3” twice as many times compared to “2”).…”
Section: Discussionsupporting
confidence: 88%
“…All surgeons used an interference screw for tibial fixation. Mahnik, et al [ 26 ] in their study found that routinely used femoral fixation methods are suspensory fixation (62%), followed by cross pins (33%) and biodegradable interference screw (5%). A bioabsorbable interference screw was used in 97% of cases as a fixation method for tibial side fixation.…”
Section: Reviewmentioning
confidence: 99%
“…It is well recognised that the two most common substitutes used in ACLR are the BPTB and STG autografts as supported by the literature as well as the results reported in study three (Chechik et al, 2013;Mahnik et al, 2013;McRae et al, 2011). The BPTB autograft exhibits properties that are between two and four times stiffer than the STG autograft, indicating that less force is required to regain AP stability in the BPTB autograft when compared to the STG (Burks & Leland, 1988;Hamner, Brown, Steiner, Hecker, & Hayes, 1999;Noyes, Butler, Grood, Zernicke, & Hefzy, 1984;Suggs et al, 2003).…”
Section: Surgical Considerationssupporting
confidence: 58%